A new reality for brands: the 4.0 Era focused on the human - Abreu, Maria José (2020)
Technological advances and changes in consumer behavior have marked a new era in retail. In addition to a re-inforcement of the omnichannel approach (Retail 3.0), the changes in marketing and retail strategies aim to strengthen the unification between the online and offline world, with the introduction of new technologies centered on the human being and its purchase process. In this way, the present article addresses and contextu-alizes the so-called "digital phenomenon", which marked the transition from Retail 3.0 to Retail 4.0, focusing entirely on the consumer and their relationship with the brand. Also presents a literary revision of the concept 4.0 and the factors that led to this transformation, with a look at the current consumer and his interaction with this new reality.